Cooperative Learning Strategies in Islamic Religious Education - Rizal, Khairul; Rahman, Abd (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This study addresses the continued reliance on lecture-based instruction in Islamic Religious Education (IRE) in rural elementary schools and emphasizes the need for more interactive approaches. Using a descriptive qualitative case-study design, data were collected through classroom observations, in-depth interviews with teachers, principals, and students, as well as documentation analysis. The findings show that teachers have implemented cooperative learning models such as Think-Pair-Share (TPS), Jigsaw, Numbered Heads Together (NHT), and structured group discussions, which effectively increased student engagement, improved understanding of religious concepts, and enhanced students’ confidence in expressing their opinions. Students’ responses were generally positive, indicating that cooperative learning supports active participation and the development of Islamic social attitudes. Challenges encountered include limited instructional time, varied student characteristics, insufficient teacher training, and inadequate learning facilities, which were addressed through clearer role distribution, the selection of simpler cooperative models, and principal-supported initiatives such as policy adjustments and training plans. Overall, cooperative learning strategies are proven effective in improving the quality of IRE instruction, with implications for developing more interactive, contextual, and character-building learning in elementary schools